Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fncir.2019.00026
|View full text |Cite
|
Sign up to set email alerts
|

Lower Posttraumatic α-Synuclein Level Associated With Altered Default Mode Network Connectivity Following Acute Mild Traumatic Brain Injury

Abstract: This study aimed to investigate the changes of α-synuclein in serum and its relationship with default mode network (DMN) connectivity after acute mild traumatic brain injury (mild TBI). Fifty-two patients with mild TBI at the acute phase and 47 matched healthy controls were enrolled in the study. All participants received resting-state functional magnetic resonance imaging (fMRI) and neuropsychological assessments. Relations between the levels of α-synuclein in serum and clinical assessments were obtained usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Ye et al showed that in TBI patients, high α-synuclein is associated with greater functional connectivity; this paradoxical finding may be related to a compensatory mechanism following brain injury that utilizes this presynaptic neuronal protein. Importantly, the low levels of α-synuclein not only predicted decreased functional connectivity, but also greater post-concussional symptoms [29]. This shows that α-synuclein may be important for an outcomes-based treatment approach.…”
Section: Biomarkers In Need Of Further Research For Diagnostic Potentmentioning
confidence: 84%
See 2 more Smart Citations
“…Ye et al showed that in TBI patients, high α-synuclein is associated with greater functional connectivity; this paradoxical finding may be related to a compensatory mechanism following brain injury that utilizes this presynaptic neuronal protein. Importantly, the low levels of α-synuclein not only predicted decreased functional connectivity, but also greater post-concussional symptoms [29]. This shows that α-synuclein may be important for an outcomes-based treatment approach.…”
Section: Biomarkers In Need Of Further Research For Diagnostic Potentmentioning
confidence: 84%
“…α-Synuclein is a presynaptic neuronal protein seen in various forms of dementia. In 2019 Ye et al examined serum α-synuclein in 52 mTBI patients and 47 healthy controls using a multiplex assay (Luminex Corp, Austin, TX, USA) [29]. Patients were evaluated with functional MRI and comprehensive neuropsychological testing.…”
Section: Alpha-synuclein (α-Synuclein; 1 Study)mentioning
confidence: 99%
See 1 more Smart Citation
“…PPCS was measured continuously in 2 studies, where blood sample collection and cognitive testing was conducted at multiple timepoints (49,50). In 4 other studies, PPCS was defined as continuing to experience symptoms at 48 h, 6 days, 2 weeks, and 4 months post injury (49,(51)(52)(53).…”
Section: Ppcs/pcsmentioning
confidence: 99%
“…Fosforilasyon ve diğer yollarla aktive olan, presinaptik bölgede bulunan αsyn, sinaptik veziküllerin fizyolojisinde önemli bir rol oynar. Merkezi Sinir Sisteminde ağırlıklı olarak nöronlarda eksprese edilen 140 amino asitlik protein olan α-syn, bir dizi nörodejeneratif hastalıkta ayırt edici biyobelirteç olarak kullanılmaktadır 7 . Bu çalışmamızdaki amacımız sıçanlarda deneysel olarak oluşturulan farklı şiddetteki KT modellerinde erken dönemde serum α-syn seviyelerini incelemek ve acil serviste (AS), TBY tanısında BBT'ye alternatif olup olamayacağını araştırmaktır.…”
unclassified